A Facile and Green Route for Conversion of Bifunctional Epoxide and Vegetable Oils to Cyclic Carbonate: A Green Route to CO2 Fixation. Issue 4 (3rd February 2017) - Farhadian, Abdolreza; Gol Afshani, Meisam Babapour; Babaei Miyardan, Ahmad; Nabid, Mohammad Reza; Safari, Nasser
Abstract: A porphyrin based catalytic system with three metals of Manganese, Zinc and Iron and quaternary ammonium salt as co‐catalyst showed very high selectivity for CO2 fixation reaction of different epoxide monomers for synthesizing cyclic carbonates. The reaction showed quantitative yields under solvent‐free and atmospheric pressure. Quaternary ammonium salts were able to catalyse these reactions singlehandedly, thus their mole ratios were decreased to investigate metalloporphyrins effect. After three cycles of reusing, this catalytic system showed minor reduction in activity and no weight loss. Also, manganese porphyrin has high ability to convert bifunctional epoxides (yield 98% in 4h) and vegetable oil by CO2 (yield 99% in 30h) to cyclic carbonates at ambient condition. Abstract : For CO2 fixation reaction of different epoxides to synthesize cyclic carbonates, a porphyrin based catalytic system showed very high selectivity. Reaction showed quantitative yields under solvent‐free and atmospheric pressure. After three cycles of reusing, minor reduction in activity and no weight loss was observed. Manganese porphyrin had high ability to convert bifunctional epoxides and vegetable oil by CO2 to cyclic carbonates at ambient condition.